Fear Priming: A Method for Examining Postural Strategies Associated With Fear of Falling - Stamenkovic, Alexander; van der Veen, Susanne M.; Thomas, James S. (Frontiers in Aging Neuroscience, 2020)
Fear of falling influences postural strategies used for balance, and is key in the maintenance of independent living and quality of life as adult’s age. However, there is a distinct need for methodology that aims to specifically address and prime fear under dynamic conditions, and to better determine the role of fear in movement preparation. This preliminary study investigated how fear priming influences fear of falling in young and older individuals, and assessed how changes in fear of falling map to movement behavior. Young (21.5 ± 1.7 years, n=10) and older (58.1 ± 2.2 years) participants matched for height, weight and sex were repeatedly exposed to 4 different and incrementally challenging laboratory-based slipping perturbations during a self-initiated, goal-directed step and reach task. Both younger and older cohorts showed similar heightened perceptions in fear of falling after fear priming, and changes in peak joint excursions including reduced ankle flexion, and increased lumbar flexion after fear priming. Age-related changes were only evident in total medio-lateral center of mass displacement, with younger participants showing greater displacement after fear priming. Despite clear differences in preparatory muscle onsets relative to reach onset seen in older participants, muscle timings or co-contraction indices were not significantly different. Methods utilizing repeated exposure to varying increases of a slip-based postural challenge can successfully prime fear of falling in individuals, regardless of age.